FORMULATION OF GRANULES AND TABLETS ACTIVE INGREDIENT PARACETAMOL IBUPROFEN AND ITS EVALUATION RESULTS - Arif Wijayanto; Juvita Herdianty (Strada Journal of Pharmacy, 2021)
Granulation is a process of increasing the powder size where a powder mixture that has a small cohesive force is changed into a larger particle size. Granulation begins with mixing the required active ingredients, so that a form of active ingredient is achieved through a mixing process (Musnamar, 2005). Dry granulation (slugging) is processing active ingredient and excipient particles by pressing the dry mixture into a solid mass. After it becomes a solid mass, it is then broken down again to produce particles that are larger than the original powder (granule). Dry granulation is used for active ingredients that have an effective dose that is too high to be directly compressed, active ingredients that are sensitive to heating and humidity, active ingredients that are difficult to flow (Chaerunnisa et al, 2009). Ibu profen is a derivative of propionic acid which has strong analgesic, antipyretic and not too strong anti-inflammatory properties. Ibuprofen has a dose-dependent duration of around 9-8 hours which is longer than the half-life. The recommended dose varies depending on body mass and indication. Paracetamol has poor compactibility and fluidity, which causes difficulties during compression with drugs that have poor compactibility in large doses. It is most appropriate to use the granulation method in this practicum using the dry granulation method because ibuprofen is not resistant to heat or moisture. Prepare tools and materials, Weighing 175 grams of Acetaminophen, 100 grams of Ibuprofen, 7.3 grams of Manihot Starch (F1= 10.95 g, F2= 36.5 g, F3= 73 g), 7.3 grams of PVP, and (F1= 0, 13985 g, F2= 0.08875 g, F3=0.00845 g), mix ad homogeneously (inner phase), The resulting internal phase mixture is inserted into the die on a tablet press, until slugs are formed, with each weighing more than 500 mg. Put the slugging results into the mortar then grind slowly until granules are formed, Sift the granules with a no 12 mesh sieve. In testing the water content of F1 granules, it was found that the granules met the water content requirements because they had a percent value of less than 5%, which was 2.55% in F1. Meanwhile, water content has not yet been obtained for F2, F3 and K-, because the slugging process cannot be carried out. Testing the angle of repose F1 before compression is 24°, after compression is 25°. At F2 before compression it is 25°, at F3 before compression it is 30°. The test results of all formulations met a good angle of repose range of 25 - 30°, but did not match the formula design. In flow time testing. According to the Indonesian Ministry of Health, 2018 stated that the flow speed is good if the granules flow <10 seconds. In F1, the flow time before they become granules is 50 seconds and after they become granules it is 6.39 seconds, where these results meet the literature. Meanwhile, for F2, F3, and K-, no results were obtained after becoming granules because the formulation could not go through the slugging process.